The effect of country image and University reputation: Where to study? - Azlan Abdul, S.; Ismail, M.N. (2011)
The study focuses to know either country image or university reputation is more dominant in attracting students who have planned to further study. The samples have been taken from all over Malaysia. The analysis part use SEM and Multiple Regression to show the results. The findings show that both country image and university reputation are important. They must come together.